Age Structure Explaining a Large Shift in Homicides: The Case of the State of São Paulo - Alexandre Schneider
After reaching a historic peak by the end of the 1990s, homicides in large cities in the state of São Paulo dropped sharply. Several explanations have been advanced, most prominently improvements in policing, adoption of policies such as dry laws, and increased incarceration. In this paper, we show that demographic changes play a large role in explaining the dynamics of homicide. More specifically, we present evidence of a strong co-movement between the proportion of males on the 15-25 age bracket and homicides at the statewide and at city levels, and argue that the relationship is causal. We estimate that a 1% increase in the proportion of 15-to-24-year-old males causes a 4.5% increase in homicides.Age Structure, Demographic Change, Homicides